A Relative Timed Semantics for BPMN - Wong, P; Gibbons, J; Wong, P; Gibbons, J (Elsevier, 2009)
We describe a relative-timed semantic model for Business Process Modelling Notation (BPMN). We define the semantics in the language of Communicating Sequential Processes (CSP). This model augments our untimed model by introducing the notion of relative time in the form of delays chosen non-deterministically from a range. We illustrate the application by an example. We also show some properties relating the timed semantics and BPMN's untimed process semantics by exploiting CSP refinement. Our timed semantics allows behavioural properties of BPMN diagrams to be mechanically verified via automatic model-checking as provided by the FDR tool. © 2009 Elsevier B.V. All rights reserved.